2016
DOI: 10.5999/aps.2016.43.4.328
|View full text |Cite
|
Sign up to set email alerts
|

The Oncological Safety of Nipple-Sparing Mastectomy: A Systematic Review of the Literature with a Pooled Analysis of 12,358 Procedures

Abstract: Nipple-sparing mastectomy (NSM) is increasingly popular as a procedure for the treatment of breast cancer and as a prophylactic procedure for those at high risk of developing the disease. However, it remains a controversial option due to questions regarding its oncological safety and concerns regarding locoregional recurrence. This systematic review with a pooled analysis examines the current literature regarding NSM, including locoregional recurrence and complication rates. Systematic electronic searches were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
102
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(112 citation statements)
references
References 98 publications
7
102
1
2
Order By: Relevance
“…A number of studies have addressed the risk of nipple areola complex or skin recurrence in patients undergoing SSM and NSM. Rates of LRR in patients with smaller tumors have been reported to be between 2% and 12% and in patients with LABC, LRR rates of 2‐14% have been reported . Our study results demonstrate a low LRR recurrence rate of 3.2% in a cohort of patients who received NAC prior to NSM/SSM with IR, supporting the procedure's oncologic safety.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A number of studies have addressed the risk of nipple areola complex or skin recurrence in patients undergoing SSM and NSM. Rates of LRR in patients with smaller tumors have been reported to be between 2% and 12% and in patients with LABC, LRR rates of 2‐14% have been reported . Our study results demonstrate a low LRR recurrence rate of 3.2% in a cohort of patients who received NAC prior to NSM/SSM with IR, supporting the procedure's oncologic safety.…”
Section: Discussionsupporting
confidence: 66%
“…In a systematic review which included 3331 NSMs, the rate of partial nipple necrosis was reported in 9.1%, complete necrosis in 2.0% (range, 0‐10), skin flap necrosis in 9.5%, and overall expander‐implant loss in 3.9% . A more recent systematic review of 12 358 patients demonstrated an overall complication rate of 22.3% and an overall incidence of partial or total nipple necrosis of 5.9% . A study using the ACS‐NSQIP database showed that 6.8% of patients undergoing mastectomy with IR experienced a return to the operating room for a complication within 30‐days of operation .…”
Section: Discussionmentioning
confidence: 99%
“…Headon et al [20] conducted a pooled analysis of 12,358 NSMs to assess complications (and oncological safety). The overall complication rate was 22.3% and the nipple necrosis rate was 5.9%.…”
Section: Complicationsmentioning
confidence: 99%
“…A recent meta-analysis of nipple-sparing mastectomy (NSM) reported an overall complication rate of 22% and a nipple necrosis rate of 5.9% 91. On the other hand, the aesthetic outcome can be significantly improved by conserving the NAC 92 93…”
Section: Prophylactic Surgerymentioning
confidence: 99%